A novel magnetically-separable porous iron-oxide nanocomposite as an adsorbent for methylene blue (MB) dye. Issue 4 (December 2016) - Sehlleier, Y.H.; Hardt, S.; Schulz, C.; Wiggers, H.
Graphical abstract: In this study, efficient and magnetically separable adsorbents for the removal of organic pollutants from water are developed, which are both, environmental friendly and cheap to produce. A new type of porous iron-oxide/polymer nanocomposite was synthesized by a two-step process utilizing surface modification of gas‐phase synthesized iron-oxide nanoparticles and a subsequent polymerization process. The potential of iron-oxide/polymer composite adsorbents with a large surface area for the removal of organic components was studied using methylene blue (MB) as a test substance. Adsorption isotherms fitted well with the Langmuir isotherm model and the adsorption capacity of MB on this adsorbent was found to be as high as 298 mg/g which is several times higher than the adsorption capacity of a number of recently reported potential adsorbents. Owing to its magnetic properties, the polluted adsorbent can be easily separated from aqueous solutions. Abstract: In this study, efficient and magnetically separable adsorbents for the removal of organic pollutants from water are developed, which are both, environmental friendly and cheap to produce. A new type of porous iron-oxide/polymer nanocomposite was synthesized by a two-step process utilizing surface modification of gas‐phase synthesized iron-oxide nanoparticles and a subsequent polymerization process. The potential of iron-oxide/polymer composite adsorbents with a large surface area for the removal of organic components was studied using methylene blue (MB) as a test substance. Adsorption isotherms fitted well with the Langmuir isotherm model and the adsorption capacity of MB on this adsorbent was found to be as high as 298 mg/g which is several times higher than the adsorption capacity of a number of recently reported potential adsorbents. Owing to its magnetic properties, the polluted adsorbent can be easily separated from aqueous solutions.